Razvijanje rezilientnosti študentov preko doživljanja izkušnje inkluzije na pedagoški praksi - Drljić, Karmen; Kiswarday, Vanja (Revija za elementarno izobraževanje, 2016)
Development of the Resilience of Students through Experiencing Inclusion during Teaching Practice. The theory of resilience studies the response to stress and adversities, which is manifested in individual’s constructive response to environmental challenges. For students—future preschool teachers on teaching practice —the first concrete contact with children with special needs can represent a challenge, which due to students’ lack of experience and competence can be sometimes rather difficult. . The aim of our qualitative research was to determine how the resilience of students that attend the study programme Preschool Education at the University of Primorska, Faculty of Education was expressed through the observation of mentor’s inclusiveness and through identifying the challenges of the inclusion of children with special needs. We analysed 43 third year students’ reports on teaching practice. The results show that students identify both inclusive and non-inclusive attitudes and functioning of their mentors. Nevertheless, they describe the mentor’s inclusive statements and functioning more frequently. Furthermore, we found out that more than a half (55.8 %) of students respond proactively to the concrete inclusive experience, while 44.2 % of them respond passively. Students who are not yet capable of proactive response need support and guidance, but more importantly, they need mechanisms for building resilience gradually and autonomously, as resilience is recognised as an important and required teacher’s competence.
Keywords: resilience; students of preschool education; teaching practice; inclusion